The antorbital fenestra of Metriorhynchidae (Crocodyliformes, Thalattosuchia): Testing Its homology within a phylogenetic framework - Leardi, Juan Martín (2012)
The metriorhynchids crocodyliforms represent the only archosaurs that where fully pelagic and thieved on mesozoic marine enviroments. Consequently to this pelagic lifestyle, the metriorhynchids have many modifications on their skeleton, like reduction of the scutes, modification of the limbs into flippers, hypocercal tails, among others. Recently, inner rostral casts were found, and the development of a nasal salt gland was recognized. This salt gland was proposed to be related to a fenestra located anteriorly to the orbit, previously identified as the antorbital fenestra of the rest of the archosaurs, a structure related to paranasal air sinuses. In our contribution, we test the identity of this fenestra using the available evidence at hand and evaluating our proposals with the evolution of the rest of the features present in these marine crocodyliforms. We recognize this structure as a neomorph of the metriorhynchids, making this fenestra not comparable to the fenestrae located anterior to the orbit in the rest of the archosaurs. The modification of this structure can be interpreted as one of the many changes in this linage associated to the fully adapted marine lifestyle.